New bounds for the Ostrowski-type inequalities via conformable fractional calculus - Usta, Fuat; Budak, Hüseyin; Tunç, Tuba; Sarikaya, Mehmet Zeki (Arabian Journal of Mathematics, 2018)
In this paper, we have introduced the new upper bounds for Ostrowski-type integral inequalities by using conformable fractional integral. In accordance with this purpose, we have benefited from the Taylor expansion for conformable fractional derivatives which was introduced by Anderson.